The effectiveness of applying the economic and technological dimensions of the kingdom of Saudi Arabia’s vision 2030 to achieve the competitive advantage of the Hail Region - Alhamad, Samer Hussein; Bani Hani, Sylvia Ismail; Dakhli, Abdesselem Chedli; Almahayreh, Abdulah Salamah (Frontiers in Energy Research, 2024)
This research focuses on examining the impact of Saudi Arabia's Vision 2030 on the energy industry, specifically in the Hail region, by exploring the role of technological and economic strategies in fostering sustainable energy development. The study aims to identify key factors that facilitate the implementation of Vision 2030 to assess the current energy landscape in Saudi Arabia. By delving into the economic and technological dimensions of Vision 2030, the research seeks to determine the essential components that the Kingdom of Saudi Arabia needs to establish systems and initiatives that align with global scientific and technological advances, ensuring competitiveness and progress in the global arena. By surveying 60 faculty members from Hail University, the study employs a descriptive-analytical approach to unravel how economic activities and technological advancements collaborate to shape a sustainable and competitive energy sector. The findings highlight the crucial role of technological innovations, including advances in administrative processes, human resource management, regulatory frameworks, and technical infrastructure related to energy efficiency and renewable energy technologies. Furthermore, the study evaluates economic aspects such as labor market reforms, skill development programs, and support for emerging energy enterprises. The results underscore the positive impact of technological and economic interventions on the energy sector in the Hail region, with significant improvements in energy project management efficiency and the creation of a conducive environment for sustainable energy practices. The study reveals that the integration of technological and economic initiatives has led to notable improvements in the energy sector, reflected in average values ranging from 68% to 84%. These results underscore the fundamental role of Vision 2030 in advancing sustainable energy development and underscore the importance of leveraging economic and technological strategies to achieve energy sustainability and competitive advantage. This research contributes to understanding how Saudi Arabia's Vision 2030 is driving progress in the energy industry and emphasizes the importance of integrating economic and technological approaches in shaping a sustainable energy landscape. The findings provide valuable information for policy makers and stakeholders in the energy sector, highlighting the need for concerted efforts to harness economic and technological advancements to promote sustainable energy development. ..etc